Effect of psychological intervention on the quality of life and mental health of leukemia patients: a meta-analysis - Yin, BingLing; Liu, XiaoRong; Mao, YanQin; Han, YanQi (Frontiers in Psychology, 2025)
BackgroundCurrently, chemotherapy is the main treatment for leukemia. According to relevant reports, the first remission rate of adult patients after chemotherapy is about 60–70%, and about 1/5 of patients can improve their survival time to 5 years or longer. However, due to the lengthy process of chemotherapy, various adverse reactions may occur, leading to negative emotions such as anxiety, depression, and fear in patients, reducing their compliance with chemotherapy, and posing a great physical and psychological challenge to patients. For the diagnosis and treatment of leukemia, there is a very close relationship between psychological status and treatment effectiveness. A good mentality is beneficial for patients to better cope with the disease and prolong their survival time.MethodsRetrieve PubMed, Web of Science, Embase, Cochrane Library, CNKI, Wanfang and search for randomized controlled trials (RCTs) related to the treatment of psychological intervention on the quality of life and mental health of leukemia patients published from the establishment of the library until August 2024. The retrieved literature will be independently screened by two researchers, and the methodological quality of the included literature will be evaluated using the bias risk assessment tool recommended in Cochrane 5.1 manual, followed by data statistical analysis.ResultsA total of 1,792 patients were included in 18 studies. The results show the Self-Rating Anxiety Scale of the test group, which was significantly lower (p < 0.01, SMD: −6.65; 95% CI: −7.94–−5.35) than the control group. Self-Rating Depression Scale of the test group was lower (p < 0.01, SMD: −7.96; 95% CI: −9.52–−6.40). European Organization for Research and Treatment of Cancer Quality of Life Questionnaire Core 30 (p < 0.01, SMD: 10.76; 95% CI: 6.27–15.24) of the test group was higher and Pittsburgh Sleep Quality Index (p < 0.01, SMD: −3.17; 95% CI: −4.68–−1.67) was lower.ConclusionThe results indicated that psychological intervention can improve the level of SAS, SDS, QLQ-C30, PSQI in patients with leukemia.